Frail phenotype and mortality prediction: A systematic review and meta-analysis of prospective cohort studies. Issue 8 (August 2015) - Chang, Shu-Fang; Lin, Pei-Ling
Abstract Aim This study focused on older adults living in communities, primarily to investigate the relationship between physical frailty and mortality, and secondly to examine gender and age effects on the relationship between frailty and mortality. Background The World Health Organization indicated that frailty has become an indicator of a lack of successful aging. Systematic literature reviews have yet to focus on the association between various frailty phases and mortality. Meanwhile, few studies researched gender and age effects on the correlation between physical frailty and mortality among older adults living in communities. Design A systematic review and meta-analysis of prospective studies. Method Frailty was assessed according to the Cardiovascular Health Study by Fried et al., who defined a frail phenotype as exhibiting the following five properties: weight loss, exhaustion, weakness, low physical activity, and mobility impairment. We included original epidemiologic population-based studies, cohort surveys, systematic reviews, and meta-analyses. Study samples included only adults aged 65 years or older who lived in communities. We excluded studies investigating hospitalised, institutionalised older adults, and those that examined disease-specific targets. We performed a pooled analysis of mortality of frailty by employing a random-effects model. Results A total of 35, 538 older adults and 7994 deaths were included in the meta-analysis. We identified 11 population-based studies that examined the relationship between mortality and frailty status in older adults. Compared with robust older adults, older people with frailty have the highest risks of mortality, followed by older people in the pre-frail phase. Older men with frailty have a higher risk of mortality than do frail older women. No age threshold for mortality risk was observed. Conclusion Frailty is a prevalent and critical geriatric syndrome associated with decreased survival. Through geriatric assessment of frailty, essential information pertaining to mortality among older adults can be obtained.